Challenges of Using the School Laboratory in Teaching Chemistry from the Perspective of Secondary School Teachers in Zliten - Eriby , Munare Salem; Aburawi, Mohamed Ali (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
This study aims to identify the challenges associated with using school laboratories in teaching chemistry in secondary schools in Zliten, as perceived by chemistry teachers. It also seeks to determine the statistical significance of differences in the assessment of these challenges based on specialization, gender, and educational level. The researcher adopted the descriptive-analytical approach and used a questionnaire as the primary data collection tool. The questionnaire was divided into four main dimensions and was administered to a sample of 66 chemistry teachers during the 2023–2024 academic year. After conducting statistical analysis using SPSS, the results indicated that the level of challenges was moderate in the first dimension and high in the remaining dimensions. The most significant challenges identified included the lack of training on laboratory use, the insufficiency of laboratory equipment for conducting chemistry experiments, the poor condition of laboratory tools and materials, and the lack of adequate support from the Ministry of Education in equipping these laboratories. The findings emphasize the necessity of addressing these challenges to enhance the effectiveness of chemistry education in secondary schools in the region. Based on the results, the researcher provided several recommendations and suggestions for improvement.
Keywords: Scientific laboratory; Chemistry; Challenges; Secondary education; Zliten; Chemistry teachers